Sistem Reseller pada Transaksi Jual Beli dalam Perspektif Fikih Muamalah : Reseller System in Buying and Selling Transactions from the Muamalah Fiqh Perspective - Rosmita, Rosmita; Nur Aidah (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2025)
This research aims to find out and understand the reseller system in buying and selling transactions from the perspective of muamalah fiqh. This research uses a type of qualitative descriptive research which focuses on the study of manuscripts and texts. The results of this research found that first, the reseller system used in buying and selling transactions is a supporter in the smooth running of buying and selling transactions. As is known, a reseller is a person who resells goods after he has bought them, where he can increase or exceed the price of the goods from the initial or previous price. The reseller system nowadays is really needed because with this system buying and selling transactions can run smoothly and is very helpful for sellers in developing their products so that everyone knows them. Second, the reseller system is allowed. Because this system also includes buying and selling transactions which are permitted in Islam. Because resellers also include contracts or exchange transactions (money from the buyer and goods from the seller). So, just as buying and selling is permitted in the Qur'an and Sunah, so are resellers as long as they fulfill the terms and conditions of buying and selling.